2006
DOI: 10.1089/dia.2006.8.489
|View full text |Cite
|
Sign up to set email alerts
|

Usability of a Microtapered Needle (TN3305) for Insulin Treatment in Japanese Patients with Diabetes Mellitus: A Comparative Clinical Study with a Standard Thin Wall Needle

Abstract: The preferences and VAS scores suggested that Needle T caused less pain than Needle B. The incidence of adverse events and safety were equivalent for both needles. We believe that usability of Needle T by patients for self-injection is better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 2 publications
2
6
0
Order By: Relevance
“…*P < 0.05 was considered statistically significant for the favored needle (NanoPass 33G) vs the alternative needle (Micro Fine Plus 31G) compared using the nonlinear mixed effects model. the previous finding by Asakura et al 5 who used a shorter term than in this study. Furthermore, this study showed that the NanoPass needle causes significantly less bruising than the Micro Fine Plus needle.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…*P < 0.05 was considered statistically significant for the favored needle (NanoPass 33G) vs the alternative needle (Micro Fine Plus 31G) compared using the nonlinear mixed effects model. the previous finding by Asakura et al 5 who used a shorter term than in this study. Furthermore, this study showed that the NanoPass needle causes significantly less bruising than the Micro Fine Plus needle.…”
Section: Discussionsupporting
confidence: 80%
“…The NanoPass needle provided diabetic patients with less pain, and the usability of the NanoPass needle by patients for self-injection was better than the Micro Fine Plus needle. 5 We reevaluated usability of the NanoPass needle in comparison with the Micro Fine Plus needle in insulindependent diabetic patients and examined the factors for the difference in usability between the two needles.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a similar study examining response in 30-gauge versus 29-gauge versus 27-gauge syringe needles also showed that penetration force correlated with needle diameter. 43 Both patients and HCPs have reported less pain and greater preference for thinner needles in comparisons of 33-gauge tips versus 31-gauge needles (unblinded), 44 29-gauge versus 27-gauge in blinded multiple sclerosis patients using prefilled syringes, 45 29-gauge versus 27-gauge in blinded multiple sclerosis patients, 46 32-gauge versus 30-gauge pen needles (unblinded), 47 32-gauge versus 31-gauge pen needles, 38 and in comparison of 31-gauge needles, normal to thin wall. 48 Finally, Japanese patients found less pain and bruising using a 33-gauge needle in a crossover study with a 31-gauge comparator needle.…”
Section: Aronsonmentioning
confidence: 99%
“…Asakura et al 44 compared two different tip gauges and found less pain with a 29-gauge microtapered needle that slimmed to a 33-gauge tip. In two French trials, covering 241 patients, less pain was found with a five-bevel tip 45 that happened to be on a narrower 29-gauge needle.…”
Section: Aronsonmentioning
confidence: 99%
“…24 A clinical study conducted to evaluate injection performance of different needles upon self-injection of insulin revealed that even though the injection forces in 28G-33G microtapered needles (Terumo Corporation, Tokyo, Japan) were similar to those in standard 31G thin-wall (TW) needles (Becton-Dickinson), patients concerned about pain often preferred microtapered needle over TW needle. 25 These results suggest a potential role of tapering technology in reducing pain and discomfort of injections when compared with traditional needles. Based on these findings, to enable efficient injection of highly viscous drug products while minimizing injection forces and associated pain, Terumo Corporation recently developed the 24G-29G tapered needle (29G TNN), which combines the effects of diameter and length ( Fig.…”
Section: Introductionmentioning
confidence: 94%